Primary mediastinal germ cell tumours: an immunohistochemical and molecular diagnostic approach. Issue 2 (16th November 2021) - Fichtner, Alexander; Richter, Annika; Filmar, Simon; Kircher, Stefan; Rosenwald, Andreas; Küffer, Stefan; Nettersheim, Daniel; Oing, Christoph; Marx, Alexander; Ströbel, Philipp; Bremmer, Felix
Abstract : Aims: Primary mediastinal germ cell tumours (PMGCTs) are rare mediastinal neoplasms, and their diagnosis can be challenging, owing to small biopsy samples. The aim of this study was to develop a diagnostic algorithm using immunohistochemical staining, with a focus on novel markers, and molecular analysis of isochromosome 12p [i(12p)]. Methods and results: Paraffin‐embedded tissues of 32 mediastinal tumours were analysed with immunohistochemical staining for sal‐like transcription factor 4 (SALL4), Lin‐28 homologue A (LIN28), octamer‐binding transcription factor 3/4 (OCT3/4), D2‐40, cluster of differentiation 117 (CD117), sex‐determining region Y‐box 17, sex‐determining region Y‐box 2 (SOX2), cluster of differentiation 30, the β‐subunit of human chorionic gonadotropin (β‐hCG), GATA‐binding protein 3 (GATA3), forkhead box protein A2 (FOXA2), glypican‐3 (GPC3), α‐fetoprotein (AFP), terminal deoxynucleotidyl transferase (TdT), nuclear protein of the testis (NUT), and pan‐cytokeratin. Quantitative real‐time polymerase chain reaction was performed to investigate the i(12p) status. Fifteen seminomas, seven teratomas, one yolk sac tumour, one choriocarcinoma and seven mixed PMGCTs were diagnosed. Each entity had different immunohistochemical staining patterns, which helped to distinguish them: OCT3/4, D2‐40, CD117 and TdT for seminoma; OCT3/4 and SOX2 for embryonal carcinoma; FOXA2, GPC3 and AFP for yolk sac tumour; and β‐hCG and GATA3 for choriocarcinoma. Mature teratomas stained positively for pan‐cytokeratin in epithelial components and focally for SALL4, SOX2, GATA3, D2‐40, and FOXA2. Furthermore, a NUT carcinoma mimicking a PMGCT was diagnosed, showing strong nuclear SOX2 staining and speckled nuclear NUT staining. i(12p) was detected in 24 of 27 PMGCTs (89%). Conclusion: A diagnostic algorithm is of great importance for a reliable diagnosis of PMGCT in, usually small, tissue biopsy samples. Therefore, a combination of three to four antibodies to identify the correct histological subtype is usually necessary, in addition to morphological features. The i(12p) status serves as an additional option to indicate a germ cell origin in selected cases. Abstract :